Transition expertise and identity a study of individuals who succeeded repeatedly in life and career transitions - Connolly, Christopher 1948-; Gobet, Fernand 1962- (Cambridge University Press, 2024)
Through a systematic review of relevant literature and an analysis of in-depth interviews with key expert performers, this book examines the nature of expertise that enables individuals to make repeated successful transitions over the course of their career. Focusing on business, sports, and music, it examines the roles of motivation, cognitive flexibility, personal intelligence, generative thinking, and contextual intelligence in this process. It further shows how identity changes and adapts during a career transition and how self concept evolves over the course of a career. This book has wide appeal for academics in psychology, sports, music, and business, as well as coaches, mentors, talent management, and training organisations across these domains
Title from publisher's bibliographic system (viewed on 30 May 2024)
Keywords: Career changes / Psychological aspects; Identity (Psychology); Self-perception; Motivation (Psychology); Success